Development of a novel food product by fermentation of faba bean flour - Jayasenthu Kankanamge, Nuwandi (My University, 2024)
Faba bean (Vicia faba L.; FB) is a leguminous crop abundant in essential nutrients, and potential health-promoting properties. However, consumption of FB is sparse due to their off flavors and certain anti-nutritional factors. This study aims to develop a novel food product by fermentation of FB flour using different fermentation types and investigate the effect of sugars and acids in the fermented FB products with potentially reduced ANFs. FB flour was inoculated with 1% pure Lactiplantibacillus plantarum, 25%/ 50% Lactobacillus acidophilus-Bifidobacterium sp. fortified yogurt, 15%/ 30% mixed curd cultures to create novel fermented products (n=6, 3 replicates). The fermentations were carried out for 24 hours at 30 °C. Products were prepared by microwaving the fermented batters. The sugar and acid contents of the mixtures were analyzed using a gas chromatogram and a flame ionization detector. An increase in the lactic acid content in each sample and a lowering of pH confirmed a successful fermentation. There were significant differences in lactic acid, fructose, sucrose, and galacturonic acid before and after fermentation in every combination (t-test, p<0.05). Curd and yogurt fermentation yielded similar changes in major acids and sugars identified. This study elucidates the influence of LAB fermentation on the flavor characteristics of FB-based dairy analogs, thus laying the groundwork for further optimization of the novel food product to enhance consumer acceptance.
Keywords: FB, fermentation, lactic acid, malic acid, yogurt